Financial Well-Being Program Development - Click, Elizabeth R.; Dobbins, Mary Ann (Building Healthy Academic Communities Journal, 2020)
Background: The impact of financial well-being on health is significant. Research connects individual and organizational well-being to the strength of financial knowledge and sound finance practices among employees. Learning more about financial topics is critical for comprehensive well-being yet few articles exist which describe implementation of such initiatives within organizations. Aim: While traditional worksite wellness programs have emphasized physical activity, stress management and nutrition, an increasingly larger number of organizations want to expand beyond those categories to topics such as community health and financial well-being. Methods: A Midwestern research-intensive university has offered financial well-being programs for faculty and staff over the last three years. A description of the initiative, and each programming effort, is included within this article. Results: Numerous positive, qualitative outcomes have been experienced by program participants. Conclusions: Learn more about the evidence and practical efforts easily implemented within higher education institutions through this description of one university’s program experience and outcomes.